Odpowiedzi

2010-02-20T12:30:38+01:00
(3*½-2*3 ) (3*½+2*3 )-2(½+3 )²-3*½(½-2*3 ) = (1½-6)*(1½+6)-2*3½-
1½(½-6)= -4,5*7,5-7-2,25+9=-34

Najlepsza Odpowiedź!
2010-02-20T12:32:55+01:00
(3a-2b) (3a+2b)-2(a+b)²-3a(a-2b) dla a=½ b=3

(3a-2b)(3a+2b)-2(a+b)²-3a(a-2b) = 9a²-4b²-2(a²+2ab+b²)-3a²+6ab = 9a²-4b²-2a²-4ab-2b²-3a²+6ab= 4a²-6b²+2ab

4*(½)²-6*3²+2*½*3=4*¼-6*9+3=1-54+3=-53+3=-50
2010-02-20T12:36:44+01:00
(3a-2b)(3a-2b)-2(a+b)²-3a(a-2b)=
9a ² + 6ab-6ab - 4b ² - 2a ² + 2 b ² - 3a ²+ 6ab=
=4a ² + 6ab - 2b ²=
4* ½ ² + 6 * ½ * 3- 2*3 ²=
= 1+9-18=10-18=-8